A Way to Change Learning: Field Trips as a University Pedagogical Resource - Érika Vásquez Salazar (Revista Electronic@ Educare, 2014)
This article represents the systematization of different experiences related to educational field trips in higher education taking place between 2005 and 2012 within the Primary Education Division (DEB) at Universidad Nacional, Costa Rica. Field trips were used as an educational resource to develop attitudes and aptitudes in students from various education majors. The author proposes pedagogical field trips as a possible strategy to promote innovation in higher education and achieve a positive change in teaching and learning processes. Field trips are presented as a tool that allows students to complete their coursework in a more significant and participative manner being in contact with the educational reality and to become humanized and to reinvent themselves as persons and future teachers.